“One size doesn’t fit all”: Differentiated instruction in mobile application to improve listening proficiency of international students, a mixed methods approach - Maryana, Hira; Yusuf, Fazri Nur; Kurniawan, Eri (Proceedings of International Conference on Research in Education, 2025)
English as a Foreign Language (EFL) students in international classrooms possess different proficiency levels, making learning needs, styles, and readiness vary in various ways. The “one size fits all” strategy is not suitable to address this issue, especially in listening, the first important skill needed by EFL learners, which makes differentiation essential to be implemented. This study explores the impact and implementation of differentiated instruction in improving the listening proficiency of EFL learners in an international school. This convergent mixed-method study involved 29 students taking an online TOEFL class in an International senior high school. The scores of pre- and post-tests were analyzed using a paired sample t-test to examine students’ improvement in their TOEFL listening scores and proficiency levels. Content analysis of the participants’ learning journals and focus group discussions was used to find out how the differentiation was implemented. The results show significant improvement of the students’ TOEFL listening scores, leading to the improvement of their proficiency level through tiered materials in the English Listening Step-by-Step application, flexible grouping, and tiered assignments. Further study with a traditional face-to-face classroom and greater numbers of participants could be done to shed light on the effectiveness of differentiated instruction in improving English proficiency.
Keywords: differentiated instruction; listening proficiency; mobile-based application; standardized test; tiered instruction